Knowledge of Health Care Workers Regarding Zika Virus Infection in Baghdad City / Iraq - Atta Ah Mousa Al -Sarray (Journal of Global Pharma Technology, 2019)
Background: WHO declared that Zika virus infection as a global public health emergency of international concern. Objectives: To determine the level of knowledge of Health care workers regarding Zika virus in Baghdad city. Subjects and Methods: A descriptive; cross sectional study conducted at 41 randomly selected (multistage sample) hospitals and primary health care centers in Baghdad city, included 600 health care workers, The data collection continued for the period starting on 11th November-2018 ending on 3th March 3, 2019. Results: The results of demographic data was conducted on health care workers with their mean age (37.8±10.7) years ranging from (20-66) years and the highest percentage (34.2%) were in the age group (30-39) years and the lowest percentage(3.3) were in the age group (age>60) years, most of studied sample were females (73%) and married (71%),regarding Educational qualification the highest percentage (57%) from College and higher educational level, the lowest percentage from secondary school, the majority of studied sample (60%) were medical staff and not well informed regarding the association of Zika virus and Guillain-Barre syndrome, the diagnostic test, and management options, There knowledge was mainly gained from Internet, Radio and T.V. Conclusion: This study concluded that the health care workers had fair and acceptable knowledge regarding Zika virus in Baghdad city during the period of study . Recommendation: Co-ordinate educational programs are needed to increase the knowledge level of health care workers about Zika virus and other emerging diseases, these programs can be extended to include the medical students, travelers and pregnant women. Key words: Zika virus, Knowledge, Health care workers, Baghdad city.